Roles of IL-25 in Type 2 Inflammation and Autoimmune Pathogenesis - Deng, Chong; Peng, Na; Tang, Yuan; Yu, Na; Wang, Cuicui; Cai, Xiaoyan; Zhang, Lijun; Hu, Dajun; Ciccia, Francesco; Lu, Liwei (Frontiers in Immunology, 2021)
Interleukin-17E (IL-25) is a member of the IL-17 cytokine family that includes IL-17A to IL-17F. IL-17 family cytokines play a key role in host defense responses and inflammatory diseases. Compared with other IL-17 cytokine family members, IL-25 has relatively low sequence similarity to IL-17A and exhibits a distinct function from other IL-17 cytokines. IL-25 binds to its receptor composed of IL-17 receptor A (IL-17RA) and IL-17 receptor B (IL-17RB) for signal transduction. IL-25 has been implicated as a type 2 cytokine and can induce the production of IL-4, IL-5 and IL-13, which in turn inhibits the differentiation of T helper (Th) 17. In addition to its anti-inflammatory properties, IL-25 also exhibits a pro-inflammatory effect in the pathogenesis of Th17-dominated diseases. Here, we review recent advances in the roles of IL-25 in the pathogenesis of inflammation and autoimmune diseases.